Towards a sustainable rare disease and orphan drug ecosystem in Saudi Arabia: policy insights from a multi-stakeholder workshop - Ghada Mohammed Abozaid; Ghada Mohammed Abozaid; Hussain Abdulrahman Al-Omar; Abdulaziz Alrabiah; Asma AlMuaither; Amy Jayne McKnight (Frontiers in Pharmacology)
IntroductionRare diseases (RDs) present significant challenges worldwide, including Saudi Arabia (SA), where access to orphan drugs (ODs) is suboptimal. This study summarizes key insights from a multi-stakeholder workshop conducted in SA to explore and address challenges related to RD and OD accessibility. Strategies to improve the healthcare landscape for RDs in SA have also been recommended.MethodsA 1-day workshop, conducted at the Saudi Health Council in Riyadh, SA on 5 June 2023, gathered stakeholders from the government, private sector, pharmaceutical industry, legislators, regulators, providers, payers, academia, and insurance companies. Through a series of presentations, educational sessions, and plenary discussions, participants examined the current landscape of RDs in SA, identified barriers to accessing ODs, and recommended strategies and initiatives to improve the accessibility, innovation, and sustainability of ODs.ResultsThe workshop highlighted key challenges recognized by a diverse group of 59 participants, including the absence of a national strategy, absent of local RDs and ODs definitions in the Saudi context, limited awareness and understanding of RDs among healthcare professionals, delayed diagnoses, scarcity of treatment and diagnosis centers for RDs, insufficient screening and prevention programs, regulatory hurdles in approving and importing ODs, and financial constraints. These challenges significantly impact patient access to ODs, imposing additional burdens on patients, families, healthcare systems, and society.DiscussionThe recommended strategies to enhance RD and OD accessibility include multifaceted approaches, such as increasing medical education and awareness, accrediting and investing in expanding the number of centers of excellence for RD diagnosis and management, streamlining regulatory processes for OD approval and importation, fostering international collaborations for knowledge exchange and capacity building, and implementing national policies to improve the affordability and reimbursement of ODs. Stakeholder collaboration is crucial to overcome the accessibility challenges of RDs and ODs. The development of comprehensive national RD strategies ensures equitable resource allocation, a national RD registry, and infrastructure improvements. These measures are vital for ensuring equitable access to ODs and the efficient provision of healthcare services in SA.